The neurotoxicity of iodoacetic acid, a byproduct of drinking water disinfection - Wang, Xu; Rong, Chunshu; Niu, Ping; Leng, Wei; Wang, Gaihua; He, Ziqiao; Qi, Xin; Zhao, Dexi; Li, Jinhua (Frontiers in Toxicology, 2025)
IAA is a by-product of the water disinfection process and has been found to be neurotoxic. However, the role and mechanism of IAA neurotoxicity remain unclear. In this review, we comprehensively discuss the neurotoxic effects and mechanisms of IAA from the molecular level, cellular level and neurological manifestations. At the molecular level, IAA causes neurotoxicity by reducing mitochondrial membrane potential, aggravating oxidative stress and DNA damage. At the cellular level, IAA causes neurotoxicity by inducing BBB disruption, neuroinflammation, and apoptosis. In neurological manifestations, IAA can lead to neurotransmitter disorders, neurodevelopment dysfunction, and even neurodegenerative diseases. Taken together, our review provides insights into the mechanisms of IAA neurotoxicity that will contribute to future studies of IAA neurotoxicity and its protective strategies.